Identification of optimal surgical plan for treatment of extraocular muscle damage in thyroid eye disease patients based on computational biomechanics - Jeong, Byeong Cheol; Lee, Chiseung; Park, Jungyul; Ryu, Dongman (Frontiers in Bioengineering and Biotechnology, 2023)
This study replicated the behavior of intraorbital tissue in patients with thyroid eye disease (TED) based on finite element analysis for general orbital decompression risk evaluation in TED patients. The orbit and intraorbital tissues of TED patients who underwent orbital decompression were modeled as finite element models. The stress was examined at specific locations of the removed orbital wall of a TED patient with undergone orbital decompression, and its variation was analyzed as a function of the shape and dimension (to be removed). As a result, in orbital decompression surgery which removes the orbital wall in a rectangular shape, the stress at the orbital wall decreased as the width and depth of the removed orbital wall increased. In addition, in the case of orbital decompression, it can be seen that the chamfered model compared to the non-chamfered model (a form of general orbital decompression) have the stress reduction rate from 11.08% to 97.88%. It is inferred that if orbital decompression surgery considering the chamfered model is performed on an actual TED patient, it is expected that the damage to the extraocular muscle caused by the removed orbital wall will be reduced.